Cactus Culture for Amateurs : Being Descriptions of the Various Cactuses Grown in This Country, With Full and Practical Instructions for Their Successful Cultivation - Watson, William, 1858-1925 (Salt Lake City, UT : Project Gutenberg, 2004)
"Cactus Culture for Amateurs" by William Watson is a practical guide on the cultivation of cacti written in the late 19th century. This publication serves as a comprehensive manual designed for amateur horticulturists, detailing various species of cacti grown in England and providing straightforward instructions for their successful care and cultivation. The book aims to enhance the popularity of cacti, which at the time were considered somewhat obscure in English gardens despite their unique beauty and fascinating characteristics. At the start of the guide, the author discusses the historical context of cacti in English horticulture, noting a decline in their popularity following a previous "Cactus mania." Watson explains the unique aesthetic qualities of cacti, particularly their striking flowers and unusual forms, while tackling misconceptions about their beauty. The opening chapters set the stage for a detailed exploration, offering a glimpse into the biological and cultural significance of these plants, and hinting at the author's deep experience and expertise at the Royal Botanic Gardens, Kew. This introduction establishes the book as an essential resource for those who wish to appreciate and cultivate cacti, highlighting both their challenges and their rewards. (This is an automatically generated summary.)
Release date is 2004-09-03
Produced by W. Christie and Leonard Johnson
Keywords: Cactus